Affective and self-presentational responses to an exercise identity challenge: Investigating identity theory and the role of others. (May 2018) - Strachan, Shaelyn; Stadig, Gwenyth; Jung, Mary; Semenchuk, Brittany
Abstract: Objectives: We examined exercisers' affective and self-presentational reactions to identity confirming or disconfirming feedback in the presence of another person. Design: Randomized Experiment. Methods: Adult exercisers completed baseline measures prior to a laboratory session. Participants were randomly assigned to receive exercise identity confirming ( n  = 54) or disconfirming ( n  = 47) feedback in the presence of a confederate participant. After, participants indicated their level of agreement and completed measures of affect. Lastly, participants were provided with an opportunity for impression construction and completed an additional affect measure. Results: A MANOVA comparing groups revealed group differences, F (94, 6) = 31.88, p  < .001, Λ = .33, ɳp 2  = .67. Disconfirmed participants reported more negative and less positive affect, a greater desire to self-present differently, more public disagreement with feedback and more feedback rationalization. Groups did not differ on the number of solutions provided to exercise barriers. A regression analysis conducted on disconfirmed participants showed that satisfaction with self-presentation was negatively related to negative affect, β = −.411, t (45) = - 3.02, p  = 0.004, and explained a significant proportion of variance, R 2  = .15, F (45, 1) = 9.15, p  = 0.004; and positively related to positive affect, β = .512, t (45) = 4.03, p  = .001, and explained a significant amount of variance, R 2  = .25, F (45, 1) = 16.22, p  = .001. Discussion: Findings provide support for an understudied tenet of identity theory and suggest that exercise identity feedback from others may be a legitimate source of exercise identity feedback. Highlights: Disconfirmed participants had greater negative and less positive affect about feedback. Disconfirmed participants had greater desire to portray themselves differently. Disconfirmed participants publicly expressed less agreement with feedback. Satisfaction with self-presentation negatively associated with negative affect. Satisfaction with ability to self-present related to positive affect.